2016
DOI: 10.18267/j.efaj.156
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Disclosed Information with Emphasis on Goodwill Impairment

Abstract: Abstract:This paper focuses on an analysis of the mandatory disclosure of goodwill impairment information in compliance with the international accounting standard IAS 36. The international financial reporting standards require a wide range of disclosed information concerning the goodwill impairment such as the carrying amount of goodwill allocated to the cash generating unit, determination of the discount rate applied to areas such as cash flow projections or sensitivity analysis. Prior research on disclosure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the second part, the theoretical basis of the issue was explained along with some key references to the published articles. To date, only the paper by Boučková (2016) was published on a similar topic -Goodwill. Other papers were focused on IFRS mandatory disclosures, apart from the disclosure under IAS 38.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second part, the theoretical basis of the issue was explained along with some key references to the published articles. To date, only the paper by Boučková (2016) was published on a similar topic -Goodwill. Other papers were focused on IFRS mandatory disclosures, apart from the disclosure under IAS 38.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically this type of information forms the basis for a future decisionmaking of the potential investors considering their investment in the particular company's stock. (Boučková, 2016) Aggregating financial information for all the joint ventures or associates would not result in a useful information under IAS 31 and IAS 28, when the entity holds a different percentage of ownership interests in its joint ventures or associates. Users of financial statements requested a more detailed disclosure of joint ventures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reports of analysed companies significantly varied in the level of revenues' structural analysis and details of revenues recognition methodology provided. Boučková (2016) and the more recent study by Novák (2018) both found that the required level of goodwill disclosure is not met by Czech publicly listed companies.…”
Section: Literature Reviewmentioning
confidence: 96%
“…With our research we contribute to the available literature on company transformation in the Czech Republic, which is focused more on goodwill recognition and impairment (Boučková, 2016;Valouch and Králová, 2012), disclosure requirements (Gluzová, 2016;Nováková and Polák, 2015;Pospíšil, 2017) and other traits of M&A in the Czech Republic (Čibera, 2016;Zelenka, 2011;Vomáčková, 2006b). …”
Section: Introductionmentioning
confidence: 99%